2019
DOI: 10.1136/archdischild-2018-316045
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal cardiopulmonary transition in an ovine model of congenital diaphragmatic hernia

Abstract: ObjectiveInfants with a congenital diaphragmatic hernia (CDH) are at high risk of developing pulmonary hypertension after birth, but little is known of their physiological transition at birth. We aimed to characterise the changes in cardiopulmonary physiology during the neonatal transition in an ovine model of CDH.MethodsA diaphragmatic hernia (DH) was surgically created at 80 days of gestational age (dGA) in 10 fetuses, whereas controls underwent sham surgery (n=6). At 138 dGA, lambs were delivered via caesar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 31 publications
(35 reference statements)
2
37
1
Order By: Relevance
“…Most studies have found no difference 25,29,33,40 , one reported a decrease 27 and two studies reported an increase in lung weight 26,30 . While there was no significant difference between the two groups in our study, we found that DH lambs treated with sildenafil tended (P = 0.06) to have greater LBWR than did untreated DH lambs, but the lungs were still markedly hypoplastic in both treated (48% of historical controls) and untreated (39%) DH lambs 34 . Indeed, while dynamic lung compliance was initially (during the first 20 min) better in sildenafil-treated DH lambs, by the end of the 120-min ventilation period it was no longer different between the two groups.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Most studies have found no difference 25,29,33,40 , one reported a decrease 27 and two studies reported an increase in lung weight 26,30 . While there was no significant difference between the two groups in our study, we found that DH lambs treated with sildenafil tended (P = 0.06) to have greater LBWR than did untreated DH lambs, but the lungs were still markedly hypoplastic in both treated (48% of historical controls) and untreated (39%) DH lambs 34 . Indeed, while dynamic lung compliance was initially (during the first 20 min) better in sildenafil-treated DH lambs, by the end of the 120-min ventilation period it was no longer different between the two groups.…”
Section: Discussioncontrasting
confidence: 77%
“…We have previously shown that pulmonary blood flow (PBF) in sham‐operated controls is 2.4‐fold greater than in DH lambs. Based on the variability in that study, we determined that at least six successful animals per group would provide power of ≥ 80% with a two‐sided type‐I error of 5% to detect a 1.5‐fold increase in PBF in DH‐sildenafil lambs compared with DH‐saline lambs.…”
Section: Methodsmentioning
confidence: 99%
“…All surgical procedures were performed under general anaesthesia using intravenous sodium thiopental (Pentothal; Jurox, New Zealand) for induction and inhaled isoflurane (≈2% in room air; Isoflow, Abbot) for maintenance. Ewes (Merino X Border-Leicester) were intubated and monitored (ECG, expired CO 2 , arterial oxygen saturation (SaO 2 )) during surgery 14…”
Section: Methodsmentioning
confidence: 99%
“…At ≈80 days gestational age (dGA; term≈147 dGA), a DH was surgically created in fetal lambs as previously described 14. Following maternal midline laparotomy and hysterotomy, the fetal chest was exteriorised and incised through the left ninth intercostal space.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation